A survey of dengue viral infection in Aedes aegypti and Aedes albopictus from re-epidemic areas in the north of Thailand using nucleic acid sequence based amplification assay - Hutamai S. (2014)
Immature stages of Aedes aegypti and Ae. albopictus were collected from 17 dengue re-epidemic areas in Chiang Mai and Lampang Provinces, in the north of Thailand. They were reared to adults and tested for dengue viral RNA by a nucleic acid sequence based amplification assay (NASBA). Of a total of 9,825 Ae. aegypti and 150 Ae. albopictus examined, none of them were found positive for the virus, suggesting that transovarial transmission may be very low in the vector populations and may not play a significant role in the epidemiology of dengue infection in Thailand.